Vital Role of Glutamate Dehydrogenase Gene in Ammonia Detoxification and the Association Between its SNPs and Ammonia Tolerance in Sinonovacula constricta - Sun, Gaigai; Dong, Yinghui; Sun, Changsen; Yao, Hanhan; Lin, Zhihua (Frontiers in Physiology, 2021)
Increasing evidence has revealed accumulated ammonia will cause adverse effects on the growth, reproduction and survival of aquatic animals. As a marine benthic mollusc, the razor clam Sinonovacula constricta shows better growth and survival under high ammonia nitrogen environment. However, little is known about its adaptation mechanisms to high ammonia stress in an integrated mariculture system. In this study, we analyzed the association between the polymorphism of Glutamate dehydrogenase gene (GDH), a key gene involved in ammonia nitrogen detoxification, and ammonia tolerance. The results showed that 26 and 22 single nucleotide polymorphisms (SNPs) of GDH in S. constricta (denoted as Sc-GDH) were identified from two geographical populations, respectively. Among them, two SNPs (c.323T > C, c.620C > T) exhibited a significant and strong association with ammonia tolerance, suggesting that Sc-GDH gene could be served as a potential genetic marker for molecular marker-assisted selection (MAS) to increase survival rate and production of S. constricta. To observe the histological morphology and explored the histocellular localization of Sc-GDH, by paraffin section and hematoxylin-eosin staining, the gills were divided into gill filament (contains columnar and flattened cells) and gill cilia, while hepatopancreas was made up of individual hepatocytes. The results of immunohistochemistry indicated that the columnar cells of gill filaments and the endothelial cells of hepatocytes were the major sites for Sc-GDH secretion. Under ammonia stress (180 mg/L), the expression levels of Sc-GDH were extremely significantly downregulated at 24, 48, 72 and 96 h (P < 0.01) after RNA interference (RNAi). Thus, we can speculate that Sc-GDH gene may play an important role in the defense process against ammonia stress. Overall, these findings laid a foundation for further research on the adaptive mechanisms to ammonia-nitrogen tolerance for S. constricta.